2014
DOI: 10.1016/j.breast.2014.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to incomplete treatment of breast cancer in Kumasi, Ghana

Abstract: Purpose The burden of cancer in Africa is an enlarging public health challenge. Breast cancer in Ghana is the second most common cancer among Ghanaian women and the proportion of diagnosed patients who complete prescribed treatment is estimated to be very limited, thereby potentially adding to lower survival and poor quality of life after diagnosis. The objective of this study was to identify the patient and system factors related to incomplete treatment of breast cancer among patients. Methods This study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 28 publications
0
63
0
4
Order By: Relevance
“…In many African countries, women believe that a diagnosis of breast cancer is a death sentence, mainly because their only experience with the disease is through friends and relatives who have sought medical help when it is too late and treatment is ineffective [6]. Costs of care [18] or lack of awareness of health care coverage [19] can also be an impediment to women seeking medical care especially since costs of a biopsy, pathology, surgery, radiotherapy and chemotherapy often need to be covered by the patients. Finally, there are reports that women avoid medical care because of a fear of mastectomy [8, 20], especially given documented instances of husbands leaving their wives after such procedures [21].…”
Section: Discussionmentioning
confidence: 99%
“…In many African countries, women believe that a diagnosis of breast cancer is a death sentence, mainly because their only experience with the disease is through friends and relatives who have sought medical help when it is too late and treatment is ineffective [6]. Costs of care [18] or lack of awareness of health care coverage [19] can also be an impediment to women seeking medical care especially since costs of a biopsy, pathology, surgery, radiotherapy and chemotherapy often need to be covered by the patients. Finally, there are reports that women avoid medical care because of a fear of mastectomy [8, 20], especially given documented instances of husbands leaving their wives after such procedures [21].…”
Section: Discussionmentioning
confidence: 99%
“…At a minimum, patients face 3 or more nodes that are widely divergent [44]. A study done in Ghana found that being a member of the Islamic religion, seeking treatment at traditional healers, and a lack of awareness of national health insurance coverage for BC treatment were the main factors that affected treatment completion [45]. A hospital-based study from Ghana revealed that patients diagnosed with late-stage cancer who were put on adjuvant therapy with hormone receptor status evaluation were more adherent to the treatment guidelines compared with those that never had the hormone receptor status determined [46].…”
Section: Cancer Control In Africamentioning
confidence: 99%
“…Intervention management care program was developed by the researchers after reviewing of scientific research and review of literature [23,24] and also after assessment phase and defined needs and problems of study women the intervention management care program was a simple Arabic language.…”
Section: Intervention Management Care Programmentioning
confidence: 99%